Selected works of Mahatma Gandhi: The basic works - Gandhi, M. K.; Narayan, Shriman (Ed.) (Ahmedabad Navajivan Publishing House, 2015)
The selected works of Mahatma Gandhi, it includes almost all the basic brochures and pamphlets which were written by Gandhiji during his lifetime.
Keywords: Mahatma Gandhi